Repetitive transcranial magnetic stimulation reduces nicotine dependence and potentially modulates white matter microstructure in smokers: a pilot study by diffusion spectrum imaging - Chen, Dongyan; Li, Zhiqiang; Xie, Mei; Wang, Tao; Li, Ruiyang; Chen, Yao; Li, Siyin; Zhang, Qiaoli; Ling, Yuting; Liang, Xiaoyun; Mao, Huan; Zhai, Lihao; et al. (Frontiers in Neurology, 2025)
IntroductionThe present study aims to investigate the effects of repetitive transcranial magnetic stimulation (rTMS) on smoking cessation and white matter (WM) structure related to the mesolimbic dopamine pathway using diffusion spectrum imaging (DSI).MethodsThe rTMS over the left dorsolateral prefrontal cortex (DLPFC) was repeated 10 times in 18 smokers. Quantitative anisotropy (QA) and fractional anisotropy (FA) were calculated for the anisotropy assessment, and mean diffusivity (MD), radial diffusivity (RD) and axial diffusivity (AD) were determined for the diffusivity evaluation. Nicotine dependence, and craving and withdrawal symptoms were evaluated using the Fagerström Test for Nicotine Dependence (FTND), the short version of the Tobacco Craving Questionnaire (sTCQ), the visual analogue scale (VAS), and the Minnesota Nicotine Withdrawal Scale (MNWS).ResultsAfter 10 times of rTMS, the FTND, MNWS and VAS scores significantly decreased, when compared to baseline, and withdrawal symptoms were partially alleviated. Furthermore, cigarette consumption was significantly decreased by rTMS, and four participants completely stopped smoking after rTMS treatment. Importantly, the smokers only had a reduction of AD in the right nucleus accumbens (NAc) fibers after rTMS, and a strong positive correlation was observed between the change in cigarette consumption and change in AD values in the right NAc fibers after rTMS treatment.DiscussionThese results suggest that rTMS over the left DLPFC is a potential effective strategy for nicotine dependence and craving, which is probably due to the modulation of the right NAc fibers. The right NAc emerged as a region of interest that warrants further investigation as a potential therapeutic target.